The Psychological Effects of a Perfect Smile on Adults: A Survey - Marie, Fatimah; Alhuzaymi, Shatha; Alkhudhairy, May (Journal of Advanced Psychology, 2023)
Purpose: To investigate the psychological impact of dental aesthetics, specifically the effect of a perfect smile, on adults. Methodology: A random cross-sectional research was conducted on 200 adult patients who attended the dentistry facilities at Riyadh Elm University. To determine patient satisfaction with their overall dental look, an online questionnaire will be used. This cross-sectional research included REU patients and dentistry students. Adults over the age of 18 were all included in the study. Findings: On visible teeth numbers majority selected the second option, on the buccal corridor was option 2 and 3 equally, on smile lip line was ï¬rst while on lower lip touching again was 2 and 3r equally. The majority of them never had any problem because of mouth or teeth in word pronunciations, in the sense of taste. However, the majority have painful aching in the mouth occasionally. The majority of participants never felt embarrassed and irritable because of any teeth problem. The majority of participants never had diï¬ƒculty in their usual job doing, less satisfy and unable to function because of any teeth problem. Unique Contribution to Theory, Policy and Practice: The paper provides unique insights into the psychological impact of a perfect smile on adults, highlighting its role in enhancing self-esteem and quality of life. It suggests that aesthetic dentistry is not just about physical health but also mental well-being. These findings can guide policy development and practice in dentistry, emphasizing holistic patient care.